Analysis of Structural-Semantic and Cultural Aspects in English, French and Russian Anecdotes - LITVINENKO, E.V.; SIRAZOVA, L.S.; ZHARKYNBEKOVA, S.K. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this study is to identify and compare the structural-semantic and cultural features of anecdotes to reveal its similarities and differences in the english, french and russian languages. Based on the analysis of a small corpus of anecdotes, the present exploratory study intends to identify types of lexical relations such as homonymy, polysemy, and paronymy and their linguistic features. The findings show that a common feature of russian, english, and french national humour can be considered as criticism. RESUMEN El propósito de este estudio es identificar y comparar las características estructurales, semánticas y culturales de las anécdotas para revelar sus similitudes y diferencias en los idiomas inglés, francés y ruso. Basado en el análisis de un pequeño corpus de anécdotas, el presente estudio exploratorio pretende identificar tipos de relaciones léxicas como la homonimia, la polisemia y la paronimia y sus características lingüísticas. Los hallazgos muestran que una característica común del humor nacional ruso, inglés y francés, puede considerarse una crítica.